2015
DOI: 10.5812/pedinfect.21386
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic challenges in Urinary Tract Infections in Children

Abstract: Context: Urinary tract infections (UTIs) are among the most common infections in children that affect up to 3% of boys and 8% of girls. Delay in diagnosis and treatment causes renal injury and scars that can progress to end stage renal disease (ESRD) requiring dialysis and transplantation. Results: There are many pitfalls in diagnosis of UTIs both with urinalysis and culture methods and also in evaluating the risk factors and causes of UTIs. Conclusions: This paper reviews and discusses the common pitfalls in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The symptoms of pyelonephritis include pain of back, flank or abdomen, nausea, malaise, vomiting, and, diarrhea, but fever may be the only manifestation (4,5). Also nonspecific symptoms may be observed in newborns, including irritability, poor feeding, weight loss, and jaundice (6)(7)(8). Pyelonephritis as the most common serious bacterial infection occurs in infants lower than 24 months old, and they have fever without an obvious focus (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of pyelonephritis include pain of back, flank or abdomen, nausea, malaise, vomiting, and, diarrhea, but fever may be the only manifestation (4,5). Also nonspecific symptoms may be observed in newborns, including irritability, poor feeding, weight loss, and jaundice (6)(7)(8). Pyelonephritis as the most common serious bacterial infection occurs in infants lower than 24 months old, and they have fever without an obvious focus (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, the resistance pattern of E. coli to antibiotics has been very different in various studies. In a study conducted in Iran 2006, Sharifian et al found the highest susceptibility rate of E. coli to ceftriaxone (97.8%) and cefotaxime (95.2%) (14) , while in Iraq another pattern found. Other studies carried out in Iraq reported that E. coli was highly sensitive to imipenem and meropenem while has a high resistance profile toward cephalosporines including the third generation (9,10,30) .…”
Section: Discussionmentioning
confidence: 96%
“…coli is regarded as the most frequent uropathogen involved in community-acquired UTI (being implicated in more than half of all UTI cases), which is one of the most common diseases in the world (1,13) . Regional variation in uropathogens' antibiotic resistance profiles is likely due to different prevention and treatment strategies against UTIs or misuse of drugs and self-medication by the population in different geographic regions (14,15) . This variation urges the need for continuous monitoring to provide updated information to optimize the therapeutic selections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial origin of UTI is responsible for causing infections among children. Early diagnosis of urinary pathogens and prompt treatment can significantly reduce the complications affecting the lives of many children [ 31 ]. Otherwise, a late or undiagnosed UTI can increase negative impacts like morbidity, mortality, and medical costs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%